Characterization of the Biodistribution of a Silica Vesicle Nanovaccine Carrying a Rhipicephalus (Boophilus) microplus Protective Antigen With in vivo Live Animal Imaging - Mody, Karishma T.; Zhang, Bing; Li, Xun; Fletcher, Nicholas L.; Akhter, Dewan T.; Jarrett, Sandy; Zhang, Jun; Yu, Chengzhong; Thurecht, Kristofer J.; Mahony, Timothy J.; Mitter, Neena (Frontiers in Bioengineering and Biotechnology, 2021)
Development of veterinary subunit vaccines comes with a spectrum of challenges, such as the choice of adjuvant, antigen delivery vehicle and optimisation of dosing strategy. Over the years, our laboratory has largely focused on investigating silica vesicles (SV) for developing effective veterinary vaccines for multiple targets. Rhipicephalus microplus (cattle tick) are known to have a high impact on cattle health and the livestock industry in the tropical and subtropical regions. Development of vaccine using Bm86 antigen against R. microplus has emerged as an attractive alternative to control ticks. In this study, we have investigated the biodistribution of SV in a live animal model as well as further explored the SVs ability for vaccine development. Rhodamine labelled SV-140-C18 (Rho-SV-140-C18) vesicles were used to adsorb the Cy5 labelled the R. microplus Bm86 antigen (Cy5-Bm86) to enable detection and characterisation of the biodistribution of SV as well as antigen in vivo in a small animal model for up to 28 days using optical fluorescence imaging. We tracked the in vivo biodistribution of SVs and Bm86 antigen at different timepoints (Day 3, 8, 13 and 28) in BALB/c mice. The biodistribution analysis by live imaging as well as by measuring the fluorescent intensity of harvested organs over the duration of the experiment (28 days) showed greater accumulation of SVs at the site of injection. The Bm86 antigen biodistribution was traced in lymph nodes, kidney and liver, contributing to our understanding how this delivery platform successfully elicits antibody responses in the groups administered antigen in combination with SV. Selected tissues (skin, lymph nodes, spleen, kidney, liver and lungs) were examined for any potential toxicity by histological analysis, which confirmed the absence of any adverse effect or any other abnormalities in the tissues. This work highlights the safety of SVs for use in vaccine applications.